Design and Performance Horizontal Axis Wind Turbine Taper Type - Arfidian Rachman; Putri Pratiwi; Lucky Ashari (LP2M - Institut Teknologi Padang, 2019)
The potential of wind energy in Indonesia is sufficient for the development of renewable energy based on wind turbine, because the average wind speed ranges from 3-12 m / s. The wind that blows is dominated by West, Southwest, and Northwest winds with speeds sometimes reaching 2.5 m / s to 20 m / s. The designed wind turbine is a Taper type blade where the comparison of the tip chord to the base is 1.3: 1, with a blade length of 1 m. Where the blades are designed to be able to spin in high-speed winds and to maximize the efficiency that can be obtained. The design result that the highest peak is 59% at TSR 7 and the blades start to spin in winds of 8.7 m / s and at winds of 12 m / s the power produced reaches 3255 watts.